(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study has attempted to examine the teaching of writing at the intermediate level through the different components of the courses, including the goals and curricula, text books, teaching methods and evaluation processes. The work has confined itself to a comprehensive study of the aspect of writing alone, without regard to the other three language skills, namely, listening, speaking and reading. The assumption that writing is a ability that needs to be learned to remove other abilities should not be seen. Writing must then be learned / learned alongside the other skills near. Nevertheless, the present research concentrated exclusively on writing skills because of the immense importance given to writing both in academic and professional terms. The students choose the intermediate-level courses in accordance with their own preferences and careers. Students appear to concentrate more on the topics of the party and are distracted with English. The students repeat everything they have learned from the written material provided by faculty managers, thereby restricting the spectrum of language learning. In India, English is the school medium and is used primarily as a language for libraries. In addition, it is the form in which students are tested at schools, universities and entryways. Even employment placement centers perform written tests. Student authors need to realize that writing is a tool for survival beyond their classrooms in the real world. Owing to the value of English as a foreign language, more and more people understand the need for working or academic purposes to learn to write in English.